Spatial Multiomics Analysis Reveals Only Minor Genetic and Epigenetic Changes in Human Liver Cancer Stem-Like Cells Compared With Other Tumor Parenchymal Cells - Liu, Dan; Li, Hong; Dong, Hui; Qu, Mincheng; Yang, Liguang; Chen, Lina; Li, Yixue; Wang, Hongyang; He, Yufei (Frontiers in Cell and Developmental Biology, 2022)
Cancer stem cells (CSCs) usually account for a very small tumor cell population but play pivotal roles in human cancer development and recurrence. A fundamental question in cancer biology is what genetic and epigenetic changes occur in CSCs. Here we show that the in-situ global levels of DNA cytosine modifications, including 5-methylcytosine (5mC), 5-hydroxymethylcytosine (5hmC) and 5-formylcytosine (5fC), are similar between liver cancer stem-like (LCSL) cells and paratumor liver cells of liver cancer patients. We then developed a robust method combining immunohistochemistry, laser capture microdissection and genome sequencing with ultra-low-input cellssingle-cell sequencing techniques (CIL-seq) to study the detailed genetic and DNA methylation changes in human LCSL cells. We first used clinical samples of mixed hepatocellular carcinoma-cholangiocarcinoma (HCC-CCA) with stem cell features to investigate human LCSL cells. The CIL-seq analysis of HCC-CCA and HCC patients showed that LCSL cells had strong spatial genetic and epigenetic heterogeneity. More interestingly, although the LCSL cells had some potential key changes in their genome, they had substantially fewer somatic single nucleotide variants (SNVs), copy number alterations (CNAs) and differentially methylated regions than other tumor parenchymal cells. The cluster analysis of SNVs, CNAs, DNA methylation patterns and spatial transcriptomes all clearly showed that the LCSL cells were clustered with the paratumor liver cells. Thus, spatial multiomics analysis showed that LCSL cells had only minor genetic and epigenetic changes compared with other tumor parenchymal cells. Targeting key changes in CSCs, not just changes in bulk tumor cells, should be more effective for human cancer therapy.